Ovarian Pedicle Local Analgesia in Midline versus Flank Cat Ovariectomy - Alice Carbonari; Antonio Di Bello; Edoardo Lillo; Francesco Caprio; Matteo Burgio; Vincenzo Cicirelli; Raffaele Luigi Sciorsci; Annalisa Rizzo (Veterinary Medicine and Science)
ABSTRACT Objectives The study aimed to assess perioperative pain in cats subjected to ovariectomy, performed with a midline or flank approach, receiving a lidocaine splash on each ovarian pedicle. Methods Eighty female cats were divided into two groups: flank group (F), made up of 40 subjects ovariectomised using the flank approach, and the midline group (M), which consisted of 40 subjects using the midline approach. Each group was divided into two subgroups: the local anaesthesia group (L), consisting of 20 cats belonging to group F (LF) and 20 cats belonging to group M (LM), which received a splash of lidocaine (4 mg/kg) diluted in 0.5 mL/kg of saline solution on the ovarian pedicles before their ligation, and the control group (C), consisting of 20 cats belonging to group F (CF) and 20 cats belonging to group M (CM), which received the same splash using saline solution. Heart rate, respiratory rate and systolic blood pressure were monitored to assess intraoperative nociception response. An operator assigned postoperative pain scores following the Glasgow scale revised composite measure pain scale feline. Results Intraoperative HR and SBP and postoperative pain scores were higher in the control groups. The number of patients requiring rescue analgesia was higher in the control groups. In the midline approach, HR and SBP increased significantly during exteriorisation of both ovaries, while in the flank approach, this occurred predominantly during exteriorisation of the second ovary. Clinical Significance Concurred use of local and systemic analgesia in cats undergoing flank or midline ovariectomy may reduce intraoperative nociception and postoperative pain and reduce the need for rescue analgesia.